Desktop-Based Population Information System Design: Perancangan Sistem Informasi Kependudukan Berbasis Desktop - Efri Yandani (International Journal of Technology Vocational Education and Training, 2020)
This study discusses the design of a population information system at the ABC District Office. In processing population data in ABC District, it is still being done in the form of documents created through Microsoft Office which are not yet in the form of structured database processing. So that when the Head of the Sub-District Office needs population data in a short time, he often finds it difficult to find population data. So it is felt that it is necessary to make improvements to the ongoing system as needed by creating a computerized system so that reports are presented more quickly, precisely, and accurately.